Analisis Derajat Kejenuhan dan Biaya Kemacetan pada Ruas Jalan Utama di Kota Jambi - Hardiani Hardiani (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2015)
This study aimed to analyze: 1) The degree of saturation levels that occur on main roads in Jambi City; 2) Congestion costs borne by road users and the wider community as a result of the congestion that occurs on the main roads in Jambi City. The study was conducted with traffic counting method of survey and moving car observer method of survey. The study was conducted on Jalan Kapten A. Bakaruddin, Jambi City. To analyze the level of congestion, researcher used degree of saturation of roads equation. To calculate the cost of congestion, it was done by reducing the general cost of travel on the actual conditions with the conditions expected. Models of calculation use a method approach of LAPI ITB, MHS resulted from World Bank study in Indonesia and study approach of IHCM. The results from this research are: 1) the degree of saturation of traffic flow at peak activity is 0.89, which means